Pemisahan krom pada limbah cair industri penyamakan kulit menggunakan gelatin dan flokulan anorganik - Sugihartono Sugihartono (Majalah Kulit, Karet, dan Plastik, 2016)
The aim of the study was to determine the ability of gelatin, ferrous sulfate, aluminium sulfate, and combination of gelatin with ferrous sulfate or aluminium sulfate for total chromium content (trivalent chromium and hexavalent chromium) separation from tannery wastewater. Reduction of total chromium content in the wastewater was conducted using combination of gelatin and ferrous sulfate or gelatin and aluminium sulfate with a ratio of 4:0; 3:1; 2:2; 1:3; and 0:4 (w/w). The results showed that gelatin, ferrous sulfate, and aluminium sulfate, were able to reduce total chromium content in the wastewater. Combination of gelatin/ferrous sulfate or gelatin/aluminium sulfate as flocculants provide synergistic work in reducing the total chromium content. A 94.75% removal of total chromium content was achieved by combining gelatine and aluminium sulfate with a ratio of 3:1, clearer wastewater, and followed by reduction of degree of turbidity up to 74.47%. The total chromium content after treatment was 0.61 ppm, which met the requirements of wastewater for business and or daily activities especially for tanning industry.